Pengelolaan Kegiatan Kesiswaan Berbasis PrestasiDi Sma Muhammadiyah Purwodadi - Ichwan, Ali; , Prof. Dr. H.A Ngalim, M.M., M.Hum; , Dr. Sabar Narimo, M.M., M.Pd (2016)
Ali Ichwan. Q.100.140.183. Management of student activities at SMA Muhammadiyah Purwodadi achievement. Thesis. Graduate Muhammadiyah University of Surakarta. 2016. The purpose of this research was to determine (1) describe student achievement management planning activities in SMA Muhammadiyah Purwodadi. (2) describe the implementation of student achievement management activities in SMA Muhammadiyah Purwodadi. (3) describe the control of the management of student activities at SMA Muhammadiyah Purwodadi achievement. Data collection techniques of observation, interviews and documentation. Data analysis techniques with data collection, data reduction, data presentation, and conclusion. Test the validity of the data using triangulation The results of this study were (1) Planning a merit-based student activities in SMA Muhammadiyah Purwodadi, starting with extracurricular angket.Kegiatan charging data contained in SMA Muhammadiyah Purwodadi among others, is a sacred site and Hizbul Wathan (HW) is an extra that must be followed by students grade 10 and 11, Muhammadiyah Student Association (IPM), volley ball, basketball, music, art, reading and writing the Koran, the International Award for Young People (IAYP), Paskibra, futsal. Facilities provided by the school, funding extracurricular activities taken from Contribution of Development of Education (SPP) (2) extracurricular activities carried out starting from the 1st half of August to the 2nd half months Juni.Untuk ensure the implementation of extracurricular activities SMA Muhammadiyah Purwodadi goes well things which carry dil SMA Muhammadiyah Purwodadi principals include (a). identification extracurricular activities that take place in SMA Muhammadiyah Purwodadi, (b) The appointment of a coordinator for each of extracurricular activities for one academic year, (c). Their preparation of the work program coordinator / Pembina ekstgrakulikuler appointed and (d). Monitor the implementation of extracurricular (3) The form of management control of student activities with their coaches / coordinators from each ektrakulikuler reporting developments ekstrakulukuler in every semester that includes about (a) the presence of students in participating in extracurricular activities, (b) provision of material taught to students, (c) mastery students to the material taught, reporting of race that followed, (d) the achievement of students during the competition, (e) the feasibility of supporting infrastructure of extracurricular used.